EFFECTS OF GREEN IRON NANOPARTICLES ON BIOFILM-FORMING BACTERIA - GHOSH DASTIDAR, MADHUMITA; BS, NIVEDITHA; POOJA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of this study was to observe the effects of iron nanoparticles (FeNP) synthesized from plant source of biofilm-forming bacteria. Methods: FeNP were synthesized from Pongamia pinnata leave extracts and it was characterized using Ultraviolet-Visible Spectrophotometer, scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy, and energy dispersive X-ray Analysis. The synthesized FeNP were evaluated against bio film-forming Gram-negative Pseudomonas, Sewage organisms, and Gram-positive hay bacillus Bacillus subtilis. These biofilm-forming microorganisms were evaluated for antibiotic sensitivity. The extracellular and intracellular proteins of biofilm-forming bacteria were estimated in the presence of FeNP. Results: All these biofilm-forming microorganisms were found to be antibiotic-resistant. The green FeNP showed potential antimicrobial effectiveness against hay Bacillus, followed by Pseudomonas and sewage bacteria. These NPs inhibited the intracellular protein formation more than extracellular proteins of biofilm-forming micro-organisms. Conclusions: It can be concluded that the FeNP synthesized from plant sources were effectively inhibited the biofilm-forming microorganisms by obstructing the intracellular protein synthesis. These NPs can be used as an eco-friendly, cost-effective, and alternative molecule to treat the antibiotic-resistant biofilm- forming micro-organisms.